2020
DOI: 10.1111/trf.16207
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gamma irradiation on platelet redox state during storage

Abstract: Background As a method with insignificant adverse effects on in vitro quality of platelet concentrates (PCs), gamma irradiation is applied to abrogate the risk of transfusion‐associated graft‐vs‐host disease in vulnerable recipients. However, there is some evidence of lower posttransfusion responses and proteomic alterations in gamma‐irradiated platelets (PLTs), which raises some questions about their quality, safety, and efficacy. Since reactive oxygen species (ROS) are considered as markers of PLT storage le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 68 publications
(117 reference statements)
1
7
0
Order By: Relevance
“…Proteomic investigations have shown that gamma irradiation alters the platelet proteome 61,62 . Furthermore, gamma irradiated platelets show evidence of greater oxidative stress than non‐irradiated components 49,61 . While ROS accumulation was not directly measured in this study, many of the quality parameters assessed are endpoint markers of ROS damage, including receptor shedding, degranulation, mitochondrial dysfunction and potentiation of aggregation 50 .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Proteomic investigations have shown that gamma irradiation alters the platelet proteome 61,62 . Furthermore, gamma irradiated platelets show evidence of greater oxidative stress than non‐irradiated components 49,61 . While ROS accumulation was not directly measured in this study, many of the quality parameters assessed are endpoint markers of ROS damage, including receptor shedding, degranulation, mitochondrial dysfunction and potentiation of aggregation 50 .…”
Section: Discussionmentioning
confidence: 85%
“…The negative effects of irradiation are reportedly exerted by damage to nuclear DNA, a direct deleterious effect on cell membrane integrity or through the accumulation of reactive oxygen species (ROS). 49,50 Irradiation appears to have little impact on the standard metabolic (pH, glucose, lactate) or activation (CD62P, annexin-V) parameters during conventional platelet storage. [15][16][17][18][19][20] However, given the membrane alterations initiated by cold storage, including cytoskeletal modifications, alteration in microtubules, and ultimately a significant morphological change, 48,51,52 it seemed plausible that irradiation of platelets that had undergone these coldinduced modifications may result in further detrimental changes to the platelets, especially during extended storage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…400 × 10 9 platelets/unit). Interestingly, while several studies have shown that gamma irradiated platelets show evidence of greater oxidative stress than non‐irradiated components, 18,19 this does not seem to translate to significant alterations in the standard metabolic (pH, glucose, lactate) or activation (CD62P, annexin‐V) parameters. While markers of ROS damage were not investigated in this study, some differences were observed between irradiated and non‐irradiated components, with irradiation potentiating ADP‐induced aggregation and improving GPIbα retention.…”
Section: Discussionmentioning
confidence: 93%